Utilization of Google Meet in English Courses in the Informatics Engineering Department - Sari, Eka Resty Novieta; Nita, Sekreningsih; Putri, Hestia Nurliana (Information Technology and Science (ITScience), 2023)
Online learning is an alternative solution for reducing the chain of transmission of Covid-19. Google Meet is a video conferencing application created and developed by Google that is used for online meeting processes. The descriptive research method was used in this study. The questionnaires were distributed online using Google Forms as the research instrument. This study's population consisted of 32 students in the odd semester class 2B for the 2022/2023 academic year. The study's findings are as follows: (1) the indicator of ease of accessing Google Meet concluded that 93.74 percent of students said it was simple to access Google Meet in online learning; (2) According to the indicator of the ease of understanding online learning material with Google Meet, 87.49 percent of students said they understood online learning material with Google Meet; (3) Indicators of the efficacy of using the Google Meet application in online learning, particularly English, as many as 64.99 percent of students agree on the efficacy of using Google Meet in online learning.